Incidence Pattern of Rice Caseworm (Nymphula sp.) (Journal of Agriculture & Rural Development, 2008)
Incidence pattern of rice caseworm were studied from T. Aman (July - December) 1995 to Boro (December - May) 1998 at BRRI farm, Gazipur. Rice caseworm mostly damaged the rice plants 2 to 4 weeks after transplanting. The incidence occurred at 15th August and subsequent transplanting dates during T. Aman season and the highest leaf damage was observed in case of mid October planting. In Boro season, the incidence occurred in the late February. There were two peak incidence of caseworm in the month of August and October. Key words: Caseworm, Nymphula sp., incidence, leaf damage.